ROS regulation in gliomas: implications for treatment strategies - Yang, Yu-Chen; Zhu, Yu; Sun, Si-Jia; Zhao, Can-Jun; Bai, Yang; Wang, Jin; Ma, Li-Tian (Frontiers in Immunology, 2023)
Gliomas are one of the most common primary malignant tumours of the central nervous system (CNS), of which glioblastomas (GBMs) are the most common and destructive type. The glioma tumour microenvironment (TME) has unique characteristics, such as hypoxia, the blood‒brain barrier (BBB), reactive oxygen species (ROS) and tumour neovascularization. Therefore, the traditional treatment effect is limited. As cellular oxidative metabolites, ROS not only promote the occurrence and development of gliomas but also affect immune cells in the immune microenvironment. In contrast, either too high or too low ROS levels are detrimental to the survival of glioma cells, which indicates the threshold of ROS. Therefore, an in-depth understanding of the mechanisms of ROS production and scavenging, the threshold of ROS, and the role of ROS in the glioma TME can provide new methods and strategies for the glioma treatment. Current methods to increase ROS include photodynamic therapy (PDT), sonodynamic therapy (SDT), and chemodynamic therapy (CDT), etc., and methods to eliminate ROS include the ingestion of antioxidants. Increasing/scavenging ROS is potentially applicable treatment, and further studies will help to provide more effective strategies for the glioma treatment.